2012
DOI: 10.1104/pp.112.199778
|View full text |Cite
|
Sign up to set email alerts
|

Up-Regulation of a Magnesium Transporter GeneOsMGT1Is Required for Conferring Aluminum Tolerance in Rice    

Abstract: Magnesium (Mg)-mediated alleviation of aluminum (Al) toxicity has been observed in a number of plant species, but the mechanisms underlying the alleviation are still poorly understood. When a putative rice (Oryza sativa) Mg transporter gene, Oryza sativa MAGNESIUM TRANSPORTER1 (OsMGT1), was knocked out, the tolerance to Al, but not to cadmium and lanthanum, was decreased. However, this inhibition could be rescued by addition of 10 mM Mg, but not by the same concentration of barium or strontium. OsMGT1 was expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
127
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 58 publications
2
127
0
1
Order By: Relevance
“…There are 10 MGT homologs in the Arabidopsis genome and nine homologs in rice (Schock et al, 2000;Gebert et al, 2009). Among them, AtMGT6 in Arabidopsis and OsMGT1 in rice mediate root Mg uptake, respectively, although they differ in their gene expression patterns (Mao et al, 2014;Chen et al, 2012). In this study, we found that OsMGT1 is involved in enhancing OsHKT1;5 transport activity at least in rice.…”
mentioning
confidence: 53%
See 2 more Smart Citations
“…There are 10 MGT homologs in the Arabidopsis genome and nine homologs in rice (Schock et al, 2000;Gebert et al, 2009). Among them, AtMGT6 in Arabidopsis and OsMGT1 in rice mediate root Mg uptake, respectively, although they differ in their gene expression patterns (Mao et al, 2014;Chen et al, 2012). In this study, we found that OsMGT1 is involved in enhancing OsHKT1;5 transport activity at least in rice.…”
mentioning
confidence: 53%
“…The expression of OsMGT1 in the root mature zone was up-regulated by salt stress, although the induction was not as large as that by Al 3+ stress ( Fig. 5; Chen et al, 2012). Furthermore, different from the root tips, OsMGT1 in the root mature zone was highly expressed in the stellar tissues, especially in the root pericycle, which connects to the xylem and phloem (Fig.…”
Section: Discussion Different Roles Of Osmgt1 In Al Tolerance and Salmentioning
confidence: 93%
See 1 more Smart Citation
“…NRAT1 transports trivalent Al into the cells (Xia et al, 2010) for subsequent sequestration of Al into the vacuoles by OsALS1 (Huang et al, 2012a). In addition, the magnesium transporter gene OsMGT1 for magnesium uptake (Chen et al, 2012), a gene encoding the small Cys-rich peptide OsCDT3 (Xia et al, 2013), and the citrate transporter gene OsFRDL4 involved in Al-induced secretion of citrate (Yokosho et al, 2011) also were demonstrated to contribute to high Al tolerance in rice. Recently, two other ART1-regulated genes, OsFRDL2 encoding a citrate transporter and OsEXPA10 encoding an expansin for cell elongation in the root tips, were found to be specifically induced by Al, but their contribution to Al tolerance in rice is minor (Che et al, 2016;Yokosho et al, 2016).…”
mentioning
confidence: 99%
“…Although the expression and localization of ART1 is not induced by Al, the expression of downstream genes is up-regulated by Al within hours ). All the proteins encoded are localized at all root cells Xia et al 2010Xia et al , 2013Yokosho et al 2011;Chen et al 2012), but play different roles in Al detoxification (Fig. 4).…”
Section: Art1-mediated High Al Tolerance In Ricementioning
confidence: 99%